Anti‐glycoprotein VI mediated immune thrombocytopenia: An under‐recognized and significant entity?. Issue 2 (24th August 2017) - Rabbolini, David J.; Gardiner, Elizabeth E.; Morel‐Kopp, Marie‐Christine; Dunkley, Scott; Jahangiri, Anila; Lee, Christine S‐M.; Stevenson, William S.; Ward, Christopher M.
Abstract: Essentials Platelet function defects may cause atypical bleeding symptoms in immune thrombocytopenia (ITP). An isolated platelet defect of collagen‐induced aggregation was explored in a patient with ITP. ITP mediated by antibodies to glycoprotein (GP) VI curtail receptor function. Inclusion of GPVI in diagnostic antibody detection assays may improve their diagnostic utility. Idiopathic immune thrombocytopenia (ITP) is an autoimmune disorder characterized by relapsing/ remitting thrombocytopenia. Bleeding complications are infrequent with platelet counts above 30×10 9 /L, and this level is commonly used as a threshold for treatment. The question of another/ co‐existent diagnosis or an alternate mechanism of platelet destruction arises when bleeding is experienced with platelet counts above this threshold. We report a case of anti‐GPVI mediated ITP that was diagnosed following investigations performed to address this key clinical question. A patient with ITP experienced exaggerated bruising symptoms despite a platelet count of 91×10 9 /L. Platelet functional testing showed an isolated platelet defect of collagen‐induced aggregation. Next generation sequencing excluded a pathogenic variant of GP6, and anti‐GPVI antibodies that curtailed GPVI function were confirmed by extended platelet phenotyping. We propose that anti‐GPVI mediated ITP may be under‐recognized, and that inclusion of GPVI in antibody detection assays may improve their diagnostic utility and in turn, facilitate a better understanding of ITP pathophysiology and aid individualized treatment approaches.